The Role of Performance and Absenteeism in the Prediction of Turnover - Keller, Robert T. (Academy of Management Journal, 1984)
The article discusses research pertaining to the role of performance and absenteeism in the prediction of labor turnover relative to other predictors. Absenteeism may have played the dual role of enabling low performing employee to search for another job and to avoid a stressful job situation. The research suggests that the turnover of lower performing employees may be a benefit for the business organization if better replacements are available in the labor market. The study indicated that the awareness of low job performance was a significant source of job stress for employees with an internal locus of control orientation.